2018
DOI: 10.32394/pe.72.3.8
|View full text |Cite
|
Sign up to set email alerts
|

Etiological agents of bacterial meningitis in adults and antibiotic susceptibility of Streptococcus pneumoniae isolated between 2009-2016 from patients of Regional Specialist Hospital of Dr Wł. Biegański in Lódź

Abstract: INTRODUCTION. Bacterial meningitis (BM) is one of the most severe clinical form of infections, which is well known for an acute course and high mortality. Therefore, it is crucial to establish the etiology and antibiotic susceptibility of frequently isolated microorganisms. AIM. The aim of this study was to present the etiological agents of BM in adults and antibiotic susceptibility of Streptococcus pneumoniae. MATERIALS AND METHODS. The inpatient medical records with positive results of the cerebrospinal flui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 9 publications
2
3
0
Order By: Relevance
“…The present study showed that Streptococcus pneumonia, Staphylococcus aureus, Escherichia coli, and N. meningitidis were the predominant pathogens that caused bacterial meningitis. S. pneumoniae was the predominant pathogen, and it remains an important cause of bacterial meningitis, which is in agreement with the results of a previous study by Amaya-Villar R et al [25], Van de Beek D et al [26], Wall EC et al [27], Mook-Kanamori BB et al [28], Adriani KS et al [29], Weisfelt M et al [30], and Mirecka A [31]. However, other studies reported that N. meningitidis (18), Mycobacterium tuberculosis [20], coagulase-negative staphylococci [24], and Listeria monocytogenes [32] were the leading cause of bacterial meningitis.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The present study showed that Streptococcus pneumonia, Staphylococcus aureus, Escherichia coli, and N. meningitidis were the predominant pathogens that caused bacterial meningitis. S. pneumoniae was the predominant pathogen, and it remains an important cause of bacterial meningitis, which is in agreement with the results of a previous study by Amaya-Villar R et al [25], Van de Beek D et al [26], Wall EC et al [27], Mook-Kanamori BB et al [28], Adriani KS et al [29], Weisfelt M et al [30], and Mirecka A [31]. However, other studies reported that N. meningitidis (18), Mycobacterium tuberculosis [20], coagulase-negative staphylococci [24], and Listeria monocytogenes [32] were the leading cause of bacterial meningitis.…”
Section: Discussionsupporting
confidence: 91%
“…However, other studies reported that N. meningitidis (18), Mycobacterium tuberculosis [20], coagulase-negative staphylococci [24], and Listeria monocytogenes [32] were the leading cause of bacterial meningitis. Moreover, Staphylococcus aureus and Escherichia coli were the second frequent etiological agent, which is comparable with a study conducted by Mook-Kanamori BB et al (28) and Mirecka A [31].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Given that the two genes were also identi ed in close proximity to transposases within operon structures among Vietnamese isolates, it is highly probable that they will continue to disseminate. Although chloramphenicol is not commonly used in human medicine due to its bone marrow toxicity, it is still reserved for the treatment of severe infections such as certain types of meningitis, rickettsiae, or typhoid fever (101)(102)(103)(104).…”
Section: Fitness Costs Of Amr and Impact Of Amr Localization On Trans...mentioning
confidence: 99%
“…It has been used for decades as a muscle relaxant, brain and coronary vasodilator, and non-specific spasmolytic agent [26] (Figure 2). A phenylethylamine derivative, chloramphenicol, is used to treat and manage superficial eye infections such as bacterial conjunctivitis and otitis externa (Figure 2) [27,28]. Finding new therapeutic strategies, manipulating established pharmacological targets, or validating novel agents with a different mechanism of action remain the top priority.…”
Section: Introductionmentioning
confidence: 99%